2022
DOI: 10.3389/fenvs.2022.1033160
|View full text |Cite
|
Sign up to set email alerts
|

Differences in bacterial diversity, composition, and community networks in lake water across three distinct regions on the Qinghai-Tibet Plateau

Abstract: We analyze bacterial composition, diversity, geographical distribution, and their community networks in lake water in three adjacent regions on the Qinghai-Tibet Plateau (QTP). Results show that bacterial alpha-diversity indices are much lower in the Hoh Xil (HX) than that in the Yellow River Headwater (YRH) regions and the Qaidam (QD) region. The dominant phyla in QD and YRH are Proteobacteria which account for 42.45 % and 43.64 % of all detected phyla, while Bacteroidetes is the dominant bacterial taxa in HX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The α-diversity of bacteria is an indicator reflecting the abundance and community structure of bacterial populations. In this study, the diversity index of the overlying water in YZM was significantly higher than that of other sampling sites, indicating a greater species richness and more complex community structure of bacteria in YZM (Wang et al, 2023).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The α-diversity of bacteria is an indicator reflecting the abundance and community structure of bacterial populations. In this study, the diversity index of the overlying water in YZM was significantly higher than that of other sampling sites, indicating a greater species richness and more complex community structure of bacteria in YZM (Wang et al, 2023).…”
Section: Discussionmentioning
confidence: 58%
“…The environmental factors pH, ORP, water temperature, dissolved oxygen (DO), total nitrogen (TN), total phosphorus (TP), and heavy metal content are driving factors influencing the differences in bacterial community structure in lake ecosystems (Wang et al, 2023; Roguet et al, 2015; Zhong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCM showed that the migration rate (m = 0.4894) was lower than the high (m = 0.5584) and middle altitudes (m = 0.569). Therefore, the diffusion capacity of the bacterial flora at low altitudes is weak and diffusion-limited, making the bacterial community more susceptible to stochastic processes (diffusion limitation) at low altitudes [58]. Moreover, the C-score results demonstrated the importance of stochastic changes in maintaining ecosystem stability [59,60], and the SES values are larger at middle altitudes, indicating that bacterial community assembly is more influenced by deterministic processes at middle altitudes.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, some of the water from each sample was filtered through a 0.45 μm filter, and the filtrates were used to determine the dissolved organic carbon (DOC) concentration using a TOC analysis meter (TOC-LCPH, Shimadzu, Japan) based on the (HJ 501-2009, China). The total nitrogen (TN), ammonia nitrogen (NH 4 + -N), nitrate nitrogen (NO 3 − -N), nitrite nitrogen (NO 2 − -N), and total phosphorous (TP) of each water sample were monitored using gas-phase molecular absorption spectrometry at a detection limit of 0.0003 mg/L according to the standard methods [ 22 ]. Meanwhile, the longitude, latitude, and altitude were detected by a portable global positioning system (GPS-China) when the water samples were gathered, and they are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%